(untitled) (The Conference Hub, 2025)
The article emphasizes that the use of modern technologies is an important factor in improving the quality and efficiency of natural sciences. The article presents opinions on the free use of multimedia-based activities in improving educational efficiency, consolidating knowledge, and forming practical skills and competencies. The application of methods for using innovative technologies in teaching natural sciences, their advantages, and examples are covered in the section of topics based on the methods.